(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Hancornia speciosa is a fruitful species from Cerrado biome with high economic potential. However, the intense and disordered extractivism have caused a reduction of its population in its endemic area. In addition, seed recalcitrance negatively affects the conventional conservation of the species. Aiming to find alternatives that enable the long-term conservation of this species, the study’s objective was to assess the behavior of lateral bud’s regrowth after cryopreservation procedures by encapsulation-vitrification technique. Sodium alginate capsules containing lateral buds were pre-cultured in liquid WPM supplemented with 1.0 M glycerol, and subsequently exposed to different concentrations of sucrose (0.3; 0.75 and 1.0 M) for 24 or 48 hours. The capsules were subjected to dehydration in silica gel or airflow hood for 0, 1, 2 and 3 hours before different incubation times in PVS2 (0, 15, 30, 60 and 120 minutes) at 0°C. A high regeneration percentage of lateral buds was observed after cryopreservation of capsules treated with 0.75 M sucrose plus 1.0 M glycerol (24 hours), associated with dehydration in an airflow hood (1 hour) and immersion in PVS2 (15 minutes). Encapsulation-vitrification allowed the long-term conservation, and provided high plant material survival rates after cryopreservation of Hancornia speciosa sensitive explants.